STRENGTHENING ACHIEVEMENT MOTIVATION, EMOTIONAL INTELLIGENCE, AND COMMITMENT ON PERFORMANCE IMPROVEMENT EFFORTS: Empirical Study of Private Elementary School Buddhist Education Teachers in Banten - Triroso, Triroso; Hardhienata, Soewarto; Sunaryo, Widodo (Journal of Industrial Engineering & Management Research, 2022)
This study aims to find strategies and ways to improve the performance of Buddhist education teachers at private elementary schools in Banten Province by analyzing the relationship between achievement motivation, emotional intelligence, commitment to the profession and teacher performance. The method used is correlational analysis method to see the strength of the relationship between variable and indicator analysis using the SITOREM method to find out how to strengthen the variables of achievement motivation, emotional intelligence, and commitment to the profession with teacher performance. The population of this study were teachers of Buddhist education in private elementary schools in Banten Province as many as 159 teachers and a sample of 114 teachers. The results of the study using correlational analysis showed that there was a positive and significant relationship between the three independent variables, namely achievement motivation (X1), emotional intelligence (X2). ) and commitment to the profession (X3) with teacher performance (Y) with the value of the correlation coefficient, respectively ry1 = 0.221, ry2 = 0.252, ry3 = 0.256, ry12 = 0.311, ry13 = 0.275, ry23 = 0.310 and ry123 = 0.321. Based on the analysis of indicators using the SITOREM method, it shows that the achievement motivation variable can be strengthened by improving the indicators of setting goals with moderate levels of difficulty and exploring self-ability maximally to achieve targets above the standard and maintaining indicators of strong desire to obtain feedback on performance, self-emotional assessment. and the desire to complete the work based on his personal abilities. For the emotional intelligence variable, it can be strengthened by improving indicators of the use of emotions to facilitate the performance of self-emotional assessment and maintaining indicators of emotional regulation in oneself and the emotional assessment of others, as well as the commitment variable to the profession can be strengthened by improving indicators of self-identification and maintaining indicators of voluntary work. cost estimates, problems that arise, work commitments, work ethic.